Robot Pemetik Buah Melon Dengan Sortasi Berat - Muhammad Shubhi Maulana; Ridwan Siskandar; Mochamad Farras Fauzan; Joddy Lintar Balle; Tria Febriyanti; Vandame Ronald Suhada; Naufal Alif Falah; Merry Ardelia Wirastuti; Nabila Fakhiratunisa; Kaisar Renaisance Al-ars; Diana Putri Rahmani; Billi Rifa Kusumah (Jurnal Sains Indonesia, 2021)
In order to implement IoT in agriculture, a tool was designed that aims to facilitate the picking process of melons on hydroponic plantations using Blynk Software and ESP8266 components. Melon fruit picker tool is designed in the form of a robot that can be controlled via Smartphone. There is a DC motor which functions to move the position of the robot and cut melon fruit stalks. Sorting feature is also added to separate the fruit has been picked into the storage container based on the weight of the fruit. To make it easier for users to control this robot, an ESP32CAM component is added as a camera that can be accessed via Smartphones in real time.